From the nation state to Europe : essays in honour of Jack Hayward - Hayward, Jack Ernest Shalom; Menon, Anand, 1965-; Wright, Vincent; Oxford University Press (Oxford ; New York : Oxford University Press, 2001)
The relationship between the European Union and its member states is complex and evolving. This book explores not only the nature of this relationship, but also the broader implications of European integration for the ways in which the subject of European politics is studied.
Monetary sovereignty, domestic policies, and intergovernmental accord / Elie Cohen -- National squares and European circle: the challenge of adjustment / Yves Mény -- State, Europe, and republic / Pierre Grémion -- Two French changes / Stanley Hoffman -- The further off from England: British public opinion and Europe / Hugh Berrington and Rod Hague -- Policy-making in the EU: familiar ambitions in unfamiliar settings / Jeremy Richardson -- Constitutional reform and treaty reform in Europe / David Hine -- The European Union and the bureaucratic mode of production / Edward C. Page -- Image and illusion in the design of the EMU / James Forder -- Interacting states / Bruno Jobert -- Breaking open black boxes: the implications for sociological theory of European integration / Colin Crouch -- The evolution of economic policy-making in the European Union / Peter Hall.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: European Union; European Union; European Union countries -- Politics and government; European Union countries -- Economic policy; European Economic Community countries -- Economic policy; Pays de l'Union européenne -- Politique économique.; LAW -- International; Economic policy; Politics and government; European Union countries